(untitled) (Psychology Travelogs, 2024)
The article presents a theoretical study of the psychological impact of advertising on consumers in the process of choosing and purchasing fashion brands. It is revealed that owning branded goods plays a significant role in shaping self-esteem and consumer social identity. Additionally, the influence of advertising on consumers is substantial, as it contributes to brand recognition, association formation, increases visibility, and stimulates the desire to purchase the product through visual and emotional strategies. The choice of purchasing branded clothing by consumers is determined by a series of objective and subjective factors. Identified signs indicate negative emotions and stress associated with the inability to make a purchase, which subsequently affects the psychological and physical health of the consumer. It is established that advertising strategies, such as using celebrities and presence on social media, can stimulate demand for branded items but may also lead to increased spending and excessive expectations. The use of manipulative techniques in advertising influences consumers to make purchases, creating an artificial need for the product, using emotional influence, reinforcing social pressure, or creating an illusion of exclusivity. Most consumers perceive purchasing branded items as a means of supporting their status and identity, which can lead to dependence on material possessions and loss of authenticity. The potential for further research into the impact of brand consumption on social relations and consumers’ emotional state is outlined with the aim of developing effective interventions. It is expected that the study will focus on understanding this phenomenon across various social groups and determining ways to regulate it, including controlling advertising practices to reduce their influence on consumers.